Survey data on gender in relation to youth political discussion and involvement at a Public University in Ghana - Ewemooje, Olusegun Sunday (Data Brief, 2020)
This article presents extensive description of survey data on the political participation of 913 male and female undergraduate students at the University of Ghana. Multi-stage and other sampling procedures were employed to collect the data that took place between 2016 and 2017. Data were analysed using frequencies, percentages and cross-tabulations for each gender separately. The findings revealed that females reported discussing politics more frequently with others than their male counterparts, in addition, ethnicity significantly associated with political discussion and religion significantly associated with political involvement for females. However, males expressed interest and involvement in political activities at both national and student levels more frequently than their female counterparts. The findings support much of the observations in the political behavior literature. Despite the gender imbalance, respondents were partial to engagement in student politics than national politics. It is, therefore, advisable that political parties focus their recruitment efforts on university campuses.